Bahasa Dan Identitas Budaya Dalam Proyeksi Masa Depan: Pendekatan Futurologi Novel Bumi Cinta - Siddik, Achmad Muafi; Rizam, Masyithah Maghfirah (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2025)
This research highlights the importance of preserving language and cultural identity in an increasingly powerful era of globalization. Globalization and information technology accelerate cultural interaction but also promote the homogenization of values thru the dominance of foreign languages. Using the novel Bumi Cinta as the research object, this study analyzes cultural encounters thru the characters of Ayas and Ilena. With a literary futurology approach, this research explores the role of language as resistance to globalization and the transformation of cultural identity. The novel